Modified combustion synthesis of ZnO nanoparticles using renewable fuel - Shah N.N.H.; Misran H.; Razak N.A.A.; Salim M.A.; Othman S.Z.; Manap A. (Institute of Physics Publishing, 2023)
Zinc oxide nanoparticles were successfully synthesized using cost effective modified combustion synthesis route employing zinc nitrate hexahydrate as oxidant and palm oil derived C8 fatty alcohol as fuel in various ratios. The calcined zinc oxide exhibited hexagonal phase with wurtzite structure. The crystallite sizes of the samples were ranging from ca. 28 to 40 nm. Therefore, palm oil derived C8 fatty alcohol successfully played the role as low-cost and renewable fuel to synthesize zinc oxide nanoparticles. Published under licence by IOP Publishing Ltd.